Biomarker in cardiology: DGK welcomes ESC Munich 2018 - Katus, Hugo; Giannitsis, Evangelos (Clinical research in cardiology, 2018)
Biomarkers have become essential tools for diagnosis and risk stratification in cardiology. This update provides an overview on the development and clinical application of selected biomarkers with a focus on cardiac troponins (cTn). We will specifically indicate the contribution of members of the German Cardiac Society to the field both in test development and evaluation as well as application in clinical care settings. Furthermore, we briefly touch on the development of novel biomarkers and expanded applications in personalized medicine and as companion diagnostics.
Gesehen am 10.12.2019